Development and statistical optimization of nefopam hydrochloride loaded nanospheres for neuropathic pain using Box-Behnken design - S. Sukhbir; S. Yashpal; A. Sandeep (Elsevier, 2016)
Nefopam hydrochloride (NFH) is a non-opioid centrally acting analgesic drug used to treat chronic condition such as neuropathic pain. In current research, sustained release nefopam hydrochloride loaded nanospheres (NFH-NS) were auspiciously synthesized using binary mixture of eudragit RL 100 and RS 100 with sorbitan monooleate as surfactant by quasi solvent diffusion technique and optimized by 35 Box-Behnken designs to evaluate the effects of process and formulation variables. Fourier transform infrared spectroscopy (FTIR), differential scanning calorimetric (DSC) and X-ray diffraction (XRD) affirmed absence of drug-polymer incompatibility and confirmed formation of nanospheres. Desirability function scrutinized by design-expert software for optimized formulation was 0.920. Optimized batch of NFH-NS had mean particle size 328.36 nm ± 2.23, % entrapment efficiency (% EE) 84.97 ± 1.23, % process yield 83.60 ± 1.31 and % drug loading (% DL) 21.41 ± 0.89. Dynamic light scattering (DLS), zeta potential analysis and scanning electron microscopy (SEM) validated size, charge and shape of nanospheres, respectively. In-vitro drug release study revealed biphasic release pattern from optimized nanospheres. Korsmeyer Peppas found excellent kinetics model with release exponent less than 0.45. Chronic constricted injury (CCI) model of optimized NFH-NS in Wistar rats produced significant difference in neuropathic pain behavior (p < 0.05) as compared to free NFH over 10 h indicating sustained action. Long term and accelerated stability testing of optimized NFH-NS revealed degradation rate constant 1.695 × 10−4 and shelf-life 621 days at 25 ± 2 °C/60% ± 5% RH.